Lipopolysaccharide-specific memory B cell responses to an attenuated live cholera vaccine are associated with protection against Vibrio cholerae infection. Issue 20 (11th May 2018) - Haney, Douglas J.; Lock, Michael D.; Gurwith, Marc; Simon, Jakub K.; Ishioka, Glenn; Cohen, Mitchell B.; Kirkpatrick, Beth D.; Lyon, Caroline E.; Chen, Wilbur H.; Sztein, Marcelo B.; Levine, Myron M.; Harris, Jason B.
Abstract: Background: The single-dose live attenuated vaccine CVD 103-HgR protects against experimental Vibrio cholerae infection in cholera-naïve adults for at least 6 months after vaccination. While vaccine-induced vibriocidal seroconversion is associated with protection, vibriocidal titers decline rapidly from their peak 1–2 weeks after vaccination. Although vaccine-induced memory B cells (MBCs) might mediate sustained protection in individuals without detectable circulating antibodies, it is unknown whether oral cholera vaccination induces a MBC response. Methods: In a study that enrolled North American adults, we measured lipopolysaccharide (LPS)- and cholera toxin (CtxB)-specific MBC responses to PXVX0200 (derived from the CVD 103-HgR strain) and assessed stool volumes following experimental Vibrio cholerae infection. We then evaluated the association between vaccine-induced MBC responses and protection against cholera. Results: There was a significant increase in % CT-specific IgG, % LPS-specific IgG, and % LPS-specific IgA MBCs which persisted 180 days after vaccination as well as a significant association between vaccine-induced increase in % LPS-specific IgA MBCs and lower post-challenge stool volume (r = −0.56, p < 0.001). Discussion: Oral cholera vaccination induces antigen-specific MBC responses, and the anamnestic LPS-specific responses may contribute to long-term protection and provide correlates of the duration of vaccine-induced protection. Clinical trials registration: NCT01895855.